STRATEGI PENGEMBANGAN USAHA TERNAK SAPI PERAH KELOMPOK TANI NEANG MUKTI DI KECAMATAN AIR NANINGAN KABUPATEN TANGGAMUS - Rianzani, Citra; Kasymir, Eka; Affandi, Muhammad Irfan (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This study aims to analyze the internal factors, external factors and arrange development strategy on the dairy cattle business. The study was conducted by case study method at Neang Mukti Farmer Group in Air Naningan Subdistrict, Tanggamus Regency purposively. Data of this research was collected on January to March 2017. The internal factors were analyzed by Internal Factors Evaluation (IFE) matrix, while external factors by External Factors Evaluation (EFE) matrix. The analysis of development strategy and determining priority strategy were obtained by Strengths Weaknesses Opportunities Threats (SWOT) analysis and by Quantitive Strategic Planning Matrix (QSPM) analysis, respectively. The result of internal factors analysis showed that the main strength which was owned by the dairy cattle business of Neang Mukti Farmer Group was the availability of forage and water feed for livestock and its main weakness were milk production that has not been optimize and has not been tested to standardize its quality. The main opportunities of this business were the increasing national milk demand and the main threat was the existence of global warming. Finally, the strategies that could be used to develop the dairy cattle business of Neang Mukti Group were as follows: increasing the capital by lending to the bank in order to increase the scale of business, increasing the productivity of dairy cattle by utilizing the role of government institutions or universities, and cooperation with the dairy cooperatives or milk processing industry as the raw milk supplier. Key words: dairy cattle business, development strategy, QSPM, SWOT analysis